A day in space - Lord, Suzanne; Epstein, Jolie (New York : Scholastic, 1986)
Explains with simple text and pictures what it is like to walk in space, launch a satellite, eat, sleep, and brush your teeth without gravity.
3.0
K-3
Keywords: Space flight; Outer space; Outer space; Space environment